Penguatan Kesadaran Sosial Masyarakat melalui Layanan Bimbingan dan Konseling Berbasis Edukasi, Partisipasi, dan Kearifan Lokal di Desa Lobuto Timur - Desy Angio; Diva Laiya; Sri Munawarah A. Husain; Ilham Khairi Siregar; Salim Korompot; Mohamad Rizal Pautina; Jumadi Mori Salam Tuasikal; Mohamad Awal Lakadjo; Moh. Alwi Hasan (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2026)
This community service program aimed to strengthen community social awareness through the integration of Guidance and Counseling services, educational activities, community participation, and local wisdom in East Lobuto Village, Gorontalo Regency. The novelty of this program lies in applying an integrated empowerment model that combines counseling services, community education, participatory approaches, and local cultural values into a unified intervention. The program was implemented through four stages: preparation, implementation, evaluation, and follow-up. The results demonstrated improved community understanding of social issues, increased participation in collective activities, and strengthened social capital through mutual cooperation and solidarity. Collaboration among the university, village government, youth organizations, and community members supported program sustainability. This integrated approach demonstrates the potential of community-based Guidance and Counseling as an effective strategy for strengthening social awareness and promoting sustainable community empowerment.